Risk and Return Dynamics of Top Five Cryptocurrencies: A Comprehensive Analysis using an EGARCH-Based Analysis of Asymmetry and Tail Risk - Biswas, Rahul (International Journal of Engineering and Management Research, 2025)
This study examines the risk and returns dynamics of five leading cryptocurrencies—Bitcoin, Ethereum, Binance Coin, Tether, and XRP—over the period from January 2018 to December 2024. Using a combination of traditional and advanced quantitative methods, the analysis incorporates Value at Risk (VaR), Expected Shortfall (ES), and the Exponential Generalised Autoregressive Conditional Heteroskedasticity (EGARCH) model to explore asymmetry and tail behaviour in return distributions. The results show substantial heterogeneity in volatility, risk asymmetry, and persistence, particularly between speculative assets and stablecoins. Tether consistently exhibits low volatility and tail risk, reinforcing its role as a stabilising instrument. EGARCH estimates reveal significant leverage effects in Bitcoin and Ethereum, highlighting the asymmetric impact of negative news on volatility. Rolling-window statistics further capture the time-varying nature of skewness, kurtosis and volatility across assets. These findings provide empirical evidence for the importance of adaptive and asset-specific risk strategies in cryptocurrency markets and contribute to the evolving literature on digital asset risk management.